ACCOUNTING AND STATISTICS. - Mautz, Robert K. (The Accounting Review, 1945)
Abstract Accounting and statistics are much alike. Both are methods for the collection, classification, summarization, and presentation of numerical data. Each has as its goal the presentation of information in such a way that the information is clear and usable. Neither seeks to direct any action. Rather the intention in both fields is to analyze and classify the information and to indicate interrelationships within the material clearly and completely so that one who studies the reported data can readily determine what action should properly be taken. Accounting and statistics do not recommend action; they are merely service mechanisms to provide information that can be useful in the making of decisions which do lead to action. Neither accounting nor statistics should distort facts or impart to them a subjective, individualistic meaning. Thus accounting and statistics are similar in function as well as in nature. Each is concerned with the collection and presentation of information for interested parties. This is more readily apparent if the application of statistics to business is compared with accounting.